A proposal of performance indicators for collaborative business ecosystems - Graça, Paula (2017)
Business ecosystems enabled by the increasing use and improvement of communication networks, offer nowadays a powerful competitive advantage to business players and entrepreneurs. They form a collaborative new mean of economic and social value creation, addressing customers' needs, overcoming constraints of individual firms, increasing capabilities for new business opportunities, and accelerating learning and innovation. This paper proposes a set of performance indicators to measure some of these collaboration benefits, therefore motivating the sustainability and resilience of the business ecosystem. The presented results are based on simulation models, which intend to characterize the roles and interactions of a real life collaborative business ecosystem.